DINAMIKA SUBJECTIVE WELL-BEING MAHASISWA DALAM MASA PANDEMI COVID-19 - Andris Noya; Josias Taihuttu (IAKN Ambon, 2021)
This research was conducted with the aim of looking at the dynamics of student subjective well-being during the Covid-19 pandemic. The subjects in this study were students of the Ambon State Christian Religious Institute (IAKN) Pastoral Counseling Study Program. The data in the research were obtained through interviews. The interviews were conducted based on the theory of subjective well-being initiated by Diener, where subjective well-being has two main components, namely the cognitive component and the affective component. The results of the study show that students have subjective well-being which tends to be low. This is shown by the low ability of students to manage cognitive and emotional during the Covid-19 pandemic.